Cooperativity effects between regium-bonding and pnicogen-bonding interactions in ternary MF···PH3O···MF (M = Cu, Ag, Au): an ab initio study. (16th December 2020) - Zhang, Zan; Lu, Tian; Ding, Luyang; Wang, Guanyu; Wang, Zhaoxu; Zheng, Baishu; Liu, Yuan; Ding, Xun Lei
Abstract : Cooperativity effects between a regium-bonding and a pnicogen-bonding interactions in a series of MF··· PH3 O··· MF (M = Cu, Ag, Au) ternary complexes are investigated using theoretical calculations at the MP2/aug-cc-pVTZ(-PP) level. Except for the AuF··· PH3 O··· AuF complex, a pnicogen bond and a regium bond can coexist in each ternary complex. The calculated cooperativity energies are all negative, which demonstrates a positive cooperativity between the pnicogen- and regium-bonding interaction. For each series of ternary complexes, the effect of a regium-bonding interaction on a pnicogen bond is more pronounced than that of a pnicogen bond on a regium bond. Quantum theory of atoms in molecules (QTAIM), electron density difference (EDD) and natural bond orbital (NBO) analyses are extremely useful to understand the mechanism of the cooperativity effects of pnicogen- and regium-bonding interactions. These calculations indicate enhanced charge density values, charge transfer values and second-order perturbation energies for both pnicogen- and regium-bonding interactions in the ternary complex as compared to the isolated binary systems. The cooperative mechanism of both interactions is mainly electrostatic. GRAPHICAL ABSTRACT: UF0001